Method for determining a technical resource of the power transformer of traction substations under operating conditions - Matusevych, Oleksandr; Khvorost, Mykola; Malysheva, Viktoriya (Eastern-European Journal of Enterprise Technologies, 2017)
The goal of present study is to improve a method for determining a residual technical resource and expected life cycle of power transformer of the traction substations of electrified railroads under operating conditions with the influence of different factors. Solving this task makes it possible to use technical resource of the transformer in full, to decrease economic costs and labor expenses. It was established that even after a normative period of operation a substantial part of power transformers at the traction substations of railroads retains working ability under conditions of compliance with permissible load regimes, timely conducting of tests, diagnosis and maintenance. We improved a method for determining a technical resource of power transformer by introducing the rate of change in the relative wear of insulation. The essence of improvement consists in the comprehensive account of the content of indicators of humidity in a solid insulation, the content of acids and oxygen in the oil, rate of an increase in their concentration in the calculation of technical resource and the remained time of operation of the transformer. The given method allowed us to increase the accuracy of calculation of the residual resource of a transformer by 10…12 %, which enables effective planning of the substantiated periodicity and the volumes of operations on the restoration of technical resource over entire life cycle.